Fungi from Galleries of the Emerald Ash Borer Produce Cankers in Ash Trees - Nickolas N. Rajtar (MDPI AG, 2021)
The emerald ash borer (EAB, Agrilus planipennis) is a devastating invasive pest that has killed millions of ash trees in the United States and Canada. EAB was discovered in the US in 2002 and first reported in Minnesota in 2009. It attacks ash trees that are native to the United States, including Fraxinus americana (white ash), F. nigra (black ash) and F. pennsylvanica (green ash). It also attacks Chionanthus virginicus (white fringe tree). Seven species of fungi isolated and identified only from EAB-infested trees in a previous study as having the potential to cause cankers were used to test their pathogenicity in F. americana (white ash). The fungi used were Cytospora pruinosa, Diplodia mutila, Diplodia seriata, Paraconiothyrium brasiliense, Phaeoacremonium minimum, Phaeoacremonium scolyti, and Thyronectria aurigera. Two field experiments that used F. americana used two inoculation methods: woodchip and agar plug inoculations. Results indicated that all of the fungi tested caused cankers in varying amounts, as compared to the controls. The largest cankers were caused by D. mutila (270 mm2), C. pruinosa (169 mm2), and D. seriata (69 mm2). All fungi except for T. aurigera were re-isolated and sequenced to confirm Kochs’ postulates. Canker-causing fungi found in association with EAB galleries have the potential to contribute to tree dieback and mortality.